Factors Influencing the Independence of Government Auditors - Hariri, Hilwani; Hasnah, Haron; Patel, Chris (LLC “СPС “Business Perspectives”, 2015)
The auditor provides assurance that the financial statements are true and fair, and prepared according to the generally accepted accounting principles. Unfortunately, many failures in corporation have caused concerns to the auditing profession. Auditors are deemed not to be independent, as reflected in many cases of companies’ financial distress around the world and in Malaysia. The current research examined whether non-audit services fees, audit competition and audit tenure would influence perceived auditors’ independence of government auditors. Questionnaires were distributed among the respondents to rate auditors’ independence based on eight scenarios. Each of the auditor-client conflict scenarios consisted of eight different manipulations of independent variables. For the purpose of this study, two other variables, namely client’s financial position and client’s company size were controlled. The respondents were required to rate their perceptions of auditors’ independence on a Likert scale. Overall, 73 government auditors participated in this study. The findings indicate that high non-audit service and high audit competition affect the perceptions of auditors’ independence. Also, the government auditors have been found to be consistent in their judgment. The current research contributes to the accounting research knowledge in two ways. First, the framework of the current research supported by the Brunswick Lens Model could explain the outcomes. Second, providing evidence that the government auditors are reliable would lead to producing quality judgment.